Orbiviruses and bunyaviruses from a seabird colony in Scotland - Nuttall, P A; Carey, D; Reid, H W; Harrap, K A (Journal of general virology, 1981)
Viruses isolated from ticks (Ixodes uriae) and a kittiwake (Rissa tridactyla) from a seabird colony at St. Abb's Head, Scotland, were shown by complement fixation tests (CFT) to be antigenically related to the Uukuniemi and Kemerovo serogroups. Electron microscopic examination of cell cultures infected with the Kemerovo group viruses revealed particles characteristic of orbiviruses, 72 +/- 3 nm in diam., with an inner core 37 +/- 3 nm in diam., in association with intracytoplasmic, densely staining granular areas, and with fibrillar and tubular structures. Cell cultures infected with the Uukuniemi group viruses revealed characteristic bunyavirus particles, 94 +/- 7 nm in diam., with a closely adherent envelope. Both orbi- and bunyaviruses were isolated from two tick pools and the kittiwake. A third tick pool contained an orbivirus which cross-reacted with the other isolates in CFT and fluorescent antibody tests, but was distinguished from them by neutralization tests.